Trastuzumab Biosimilars in the Therapy of Breast Cancer – “Real World” Experiences from four Bavarian University Breast Centres - Hester, Anna; Gaß, Paul; Fasching, Peter A.; Krämer, Anne Katrin; Ettl, Johannes; Diessner, Joachim; Wöckel, Achim; Egger, Tobias; Stock, Katja; Redlin, Jutta; Andraschko, Monika; Harbeck, Nadia; Würstlein, Rachel (Geburtshilfe und Frauenheilkunde, 2020)
Introduction With the introduction of the first trastuzumab biosimilar in the summer of 2018, biosimilar antibodies for breast cancer have found their way into the area of gynaecological oncology. The switch of anti-human epidermal growth factor receptor 2 (HER2) therapy from the reference drug Herceptin® to a biosimilar has presented challenges to the clinics. In addition to structural and organisational measures, training of employees as well as patient briefing and acceptance were major challenges. The study presented here records – within the context of quality assurance – how the switch to a trastuzumab biosimilar was implemented at four Bavarian university clinics in the Purchasing Association of Bavarian University Pharmacies.Materials/Methods Questionnaires on treatment figures and the switching process were sent to breast centres and pharmacies of four Bavarian university clinics between July and December 2019. The neoadjuvant, adjuvant and metastasised anti-HER2 therapy with trastuzumab with or without pertuzumab was recorded, evaluated and summarised.Results In the anti-HER2-therapy, trastuzumab was used intravenously (i. v.) and subcutaneously. Between July and December 2018, all four clinics in the Purchasing Association switched the i. v. trastuzumab therapy from the reference drug (Herceptin) to a biosimilar (for 2018: Kanjinti®). Over 200 patients were treated with trastuzumab i. v. in each of the two half-years of 2018 (before and after the switch). The spectrum of side effects and pCR rates under therapy with the biosimilar were comparable to the experiences made with the reference drug. Three out of four clinics provided training to employees and informed patients by means of a defined information leaflet. Patient acceptance was high.Summary The anti-HER2 therapy could be switched successfully and safely to trastuzumab biosimilars at the Bavarian university hospitals. This may serve as guideline for the further implementation of biosimilars. The structures necessary for this initial switching process have been prepared with trastuzumab as an example.Einleitung Mit Einführung der ersten Trastuzumab-Biosimilars im Sommer 2018 haben biosimilare Antikörper beim Mammakarzinom Einzug in die gynäkologische Onkologie gehalten. Die Umstellung der Anti-„human epidermal growth factor receptor 2“-(HER2-)Therapie vom Referenzarzneimittel Herceptin® auf ein Biosimilar hat die Kliniken vor Herausforderungen gestellt. Neben strukturellen und organisatorischen Maßnahmen waren Schulung von Mitarbeitern sowie Patientenaufklärung und -akzeptanz wichtige Herausforderungen. Die vorliegende Studie erfasst im Rahmen der Qualitätssicherung, wie die Umstellung auf ein Trastuzumab-Biosimilar an 4 bayerischen Universitätskliniken im Einkaufsverbund Bayerischer Universitätsapotheken durchgeführt wurde.Material/Methoden Fragebögen zu Behandlungszahlen und Umstellungsprozess wurden an Brustzentren und Apotheken 4 bayerischer Universitätsklinika zwischen Juli und Dezember 2019 versandt. Die neoadjuvante, adjuvante und metastasierte Anti-HER2-Therapie mit Trastuzumab mit oder ohne Pertuzumab wurde erfasst und zusammenfassend ausgewertet.Ergebnisse In der Anti-HER2-Therapie wurde Trastuzumab intravenös (i. v.) und subkutan eingesetzt. Alle 4 Kliniken stellten die i. v. Trastuzumab-Therapie zwischen Juli und Dezember 2018 im Einkaufsverbund vom Referenzarzneimittel (Herceptin) auf ein Biosimilar (für 2018: Kanjinti®) um. In beiden Halbjahren 2018 (vor und nach Umstellung) wurden jeweils über 200 Patientinnen mit Trastuzumab i. v. behandelt. Nebenwirkungsspektrum und pCR-Raten waren unter Therapie mit dem Biosimilar vergleichbar mit den Erfahrungen beim Referenzarzneimittel. An 3/4 Kliniken wurden die Mitarbeiter im Rahmen von Fortbildungen geschult und die Patientinnen mittels eines definierten Aufklärungsbogen informiert. Es lag eine hohe Patientenakzeptanz vor.Zusammenfassung Die Anti-HER2-Therapie konnte an den bayerischen Universitätskliniken erfolgreich und sicher auf Trastuzumab-Biosimilars umgestellt werden. Dies kann als Leitfaden für weitere Biosimilar-Implementierungen dienen. Der erste Umstellungsprozess am Beispiel von Trastuzumab hat die Strukturen vorbereitet.
Keywords: HER2; breast cancer; trastuzumab; biosimilar; pCR